Improving The Numeracy Skills of Slow Learners with Ice Cream Stick Media: Single Subject Research - Nur Puji Rahayu; Lusiana Prastiwi; Windi Setiawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Numeracy ability is a basic ability that must be mastered by students especially elementary school students. Therefore, the purpose of this study is to improve the ability to count, add and subtract numbers 1-20 in slow learner students using ice cream stick media. This study uses quantitative experimental research on a single subject with an ABA design. The single subject in this study is a 1st grade student of SDN Tebul 1. There are 3 data collection methods used, namely interviews, observations and tests, while the data analysis uses visual analysis consisting of two types, namely in-condition analysis and inter-condition analysis. The results of this study concluded that ice cream stick media can improve numeracy skills in slow learner students. Based on the results of visual analysis, it was shown that in the initial baseline phase (A1) the ability to calculate the initial addition and subtraction of numbers 1-20 of slow learner students was still lacking with an average percentage of test results of 30%, after being given treatment in the intervention phase (B) by providing learning to count the addition and subtraction of numbers 1-20 using ice cream stick media, the numeracy ability of slow learner students increased by 45.33% with an average percentage of test results in the intervention phase (B) was 75.33% without overlapping data.